ANALISIS PEMILIHAN SUPPLIER KACA LEMBARAN DENGAN MENGGUNAKAN METODE FUZZY ANALYTICAL HIERARCHY PROCESS DAN TOPSIS - Bayu Bimantara; Saryatmo, Mohammad Agung; Adianto (Jurnal Mitra Teknik Industri, 2024)
PT. XYZ is a company engaged in the automotive manufacturing sector since 1984, producing various kinds of car and motorcycle mirrors, electric door mirrors, auto lamps, lamp cases, and grilles. The majority of the company's customers are large-scale automotive companies, so they want excellent product quality. In improving product quality in terms of price, materials and services, this company requires the right supplier to continue to compete and maintain the company. The problem with the company requires a method for selecting priority suppliers so that the company can meet customer demands and increase its competitiveness. To solve these problems, researchers used the Fuzzy Analytical Hierarchy Process (FAHP) method and the Technique for Orders Preference by Similarity to Ideal Solution (TOPSIS) method. Supplier selection is carried out by considering 5 criteria, 10 sub-criteria, and 5 alternative suppliers. The results of the Fuzzy AHP calculation show that the first rank is SP2 with a weight of 0.392, followed by SP1 with a weight of 0.271, SP5 with a weight of 0.134, SP3 with a weight of 0.103, and finally SP4 with a weight of 0.100. Meanwhile, in the TOPSIS calculation, SP2 was obtained as the first rank with a weight of 0.847; followed by SP1 with a weight of 0.604, then SP4 with a weight of 0.506, SP5 with a weight of 0.488, and finally SP3 with a weight of 0.486. So the conclusion from this study is Supplier 2 (SP2) as the best alternative for the company to be prioritized in ordering flat glass raw materials based on the results of weight calculations using the FAHP and TOPSIS methods.